Assessing the Caprini Score for Risk Assessment of Venous Thromboembolism in Hospitalized Medical Patients - Grant, Paul J. (Am J Med, 2015)
BACKGROUND: The optimal approach to assess risk of venous thromboembolism (VTE) in hospitalized medical patients is unknown. We examined how well the Caprini risk assessment model (RAM) predicts VTE in hospitalized medical patients. METHODS: Between January 2011 and March 2014, VTE events and risk factors were collected from non-intensive care unit (ICU) medical patients hospitalized in facilities across Michigan. Following calculation of the Caprini score for each patient, mixed logistic spline regression was used to determine the predicted probabilities of 90-day VTE by receipt of pharmacologic prophylaxis across the Caprini risk continuum. RESULTS: A total of 670 (1.05%) of 63,548 eligible patients experienced a VTE event within 90 days of hospital admission. The mean Caprini risk score was 4.94 (range 0 - 28). Predictive modeling revealed a consistent linear increase in VTE for Caprini scores between 1-10; estimates beyond a score of 10 were unstable. Receipt of pharmacologic prophylaxis resulted in a modest decrease in VTE risk (odds ratio=0.85; 95% confidence interval 0.72 - 0.99, p = 0.04). However, the low overall incidence of VTE led to large estimates of numbers needed to treat in order to prevent a single VTE event. A Caprini cut-point demonstrating clear benefit of prophylaxis was not detected. CONCLUSIONS: Although a linear association between the Caprini RAM and risk of VTE was noted, an extremely low incidence of VTE events in non-ICU medical patients was observed. The Caprini RAM was unable to identify a subset of medical patients who benefit from pharmacologic prophylaxis.